2020
DOI: 10.1007/s11356-019-07472-1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the powerful phytoarsenal of white grape marc against bacteria and parasites causing significant diseases

Abstract: Natural extracts containing high polyphenolic concentration possess antibacterial, anti-parasitic and fungicidal activities. The present research characterises two extracts based on white grape marc, a winemaking by-product, describing their physicochemical features and antimicrobial capacities. The main components of these extracts are phenolic acids, flavan-3-ols and their gallates and flavonols and their glycosides. As a result of this complex composition, the extracts showed pronounced bioactivities with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…This is due to the release of high amounts of tannins and polyphenols, together with high oxygen consumption, which could have a negative impact on wildlife growth ( 4 , 5 ). In contrast, the high content of bioactive compounds in grape marc, including both flavonoids and non-flavonoids, has shown important antioxidant and antimicrobial effects, being associated with the prevention of numerous diseases, including cardiovascular problems, neurodegenerative disorders such as Alzheimer’s, in addition to various forms of cancer ( 3 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the release of high amounts of tannins and polyphenols, together with high oxygen consumption, which could have a negative impact on wildlife growth ( 4 , 5 ). In contrast, the high content of bioactive compounds in grape marc, including both flavonoids and non-flavonoids, has shown important antioxidant and antimicrobial effects, being associated with the prevention of numerous diseases, including cardiovascular problems, neurodegenerative disorders such as Alzheimer’s, in addition to various forms of cancer ( 3 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…As previously reported, a large proportion of polyphenols enter into the colon and undergo microbial biotransformation [42]. Meanwhile, polyphenols also interact with intestinal microbiome by modulating its composition and construction, which mainly inhibits the growth of pathogens and promotes the proliferation of Akkermansia, Lactobacillus, and Bifidobacterium, thus serving as prebiotics [106][107][108]. In turn, certain probiotic strains are equipped with tannase, α-L-rhamnosidase, and phenolic acid reductase, which are responsible for the bio-transformation of polyphenols into bioactive phenolic metabolites [109].…”
Section: Animal Models Of Inflammatory Intestinal Diseasesmentioning
confidence: 88%
“…Based on these guidelines, Lores et al (2016) developed and patented a scalable extractive approach, referred to as MSAT (Medium Scale Ambient Temperature systems) for obtaining bioactive extracts at pilot scale. Its applicability on an industrial scale was subsequently demonstrated (Gato et al 2021;Rama et al 2021) processing biomasses with a moisture content up to 90% without prior pre-treatment and obtaining high yields. The development of the technique and its applications faithfully comply with the principles of green chemistry (Anastas and Warner 1998).…”
Section: Introductionmentioning
confidence: 99%